Integration Religious Literacy and the Sustainable Development Goals in Civic Education - Silvia Rahmelia; Chris Apandie (Jurnal Edukasi Terkini, 2025)
Purpose-This study examines the integration of inclusive religious literacy and sustainable development goals (based on SDGs goals 4, 12, and 16) into Civic Education (PKn) learning at the Palangka Raya State Institute Of Christian Religion. Using a qualitative approach and participatory observation over one semester,Research Methodology/Design/Approach- the study found that this integration was implemented through three main strategies: (1) contextualization of materials using local case studies, (2) application of critical dialogue based on Paulo Freire's approach, and (3) assignments for sustainable projects. Finding-The results showed that these strategies were effective in enhancing students' multicultural awareness and their ability to analyze issues of intolerance and sustainability. The challenges encountered included student resistance stemming from exclusive religious mindsets, lecturer capacity, and limited local references. However, collaboration with religious institutions and indigenous communities presented a strategic opportunity to overcome these challenges. Originality / Value-This study recommends the development of local case-based learning modules to strengthen the relevance and effectiveness of integrating these values in shaping responsible citizens.